PELATIHAN GURU BERWIBAWA UNTUK MENINGKATKAN KOMPETENSI SOSIAL DALAM MENGAJAR GURU PADA SMP â€œXâ€ - Dudona, Mira; Nugraha, Sumedi P; Gusniarti, Uly (Psikoislamedia: Jurnal Psikologi, 2016)
This study aims to measure the improvement of the teacher’s social competence in teaching junior high school in "X" before being given training (pretest) and two weeks after training (posttest). The hypothesis in this study is authoritative teacher training can improve the teacher‘s social competence in teaching junior high school "X". Teachers are given the Authoritative Teacher Training will increase the teacher’s social competence in teaching. This study is a quasi-experimental design using one group pretest, posttest and follow-up. This study used the scale of the teacher’s social competence in teaching, observation scale, and opened scale. Data were analyzed using the Wilcoxon test. The result shows that there were changes in the teacher’s social competence before being given training and two weeks after training (Wilcoxon Z = -3.660 with a value of p = 0.000 (sig